Microwave-dried amorphous silicon-based aerogel-based powder and method for preparing the same

CN122999080APending Publication Date: 2026-10-30ZHONGKE RUNZI (CHONGQING) ENERGY SAVING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611159935.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于:提供一种微波干燥制备的非晶态硅基气凝胶基粉及其制备方法,其可以解决疏水功能组分与亲水溶胶相容性差和气凝胶纳米孔结构在热加工中坍塌失效的问题

Benefits of technology

1:本发明通过相转化法预制水基构建组合物,将疏水二氧化硅、短切玻璃纤维和热膨胀胶囊预集成于SEBS-g-MAH/环烷油载体中,系统性地解决了疏水功能组分与亲水硅溶胶相容性差、热膨胀胶囊在凝胶过程中提前失效的关键难题,同时利用分段程序微波干燥与热膨胀微球原位造孔协同,在气凝胶骨架中一步构建纳米介孔与微米空腔贯通的多级孔结构,实现了低密度、高比表面积和持久疏水三重性能协同;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the application material technical field, specifically to a kind of amorphous silicon-based aerogel base powder prepared by microwave drying and a preparation method thereof;A kind of amorphous silicon-based aerogel base powder prepared by microwave drying, consisting of the following components by mass percentage: 28-30% tetraethyl orthosilicate, 23-25% anhydrous ethanol, 10-12% water-based building composition, 4-6% hexamethyldisilazane, 0.7-1% gamma-mercaptopropyl triethoxysilane, 1-1.5% hydrogen peroxide solution, 0.3-0.5% acetic acid solution, 2-3% hydrochloric acid solution, 3-4% ammonia water and 17-28% deionized water;The present application solves the problem of poor compatibility of hydrophobic components with hydrophilic sol in the preparation of existing aerogel powder and the collapse of nanopore structure in thermal processing, realizes the multiple function synergy of low density, high specific surface area, durable hydrophobicity and self-repairing of aerogel base powder, and provides a new solution for aerogel base powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of applied materials technology, specifically to an amorphous silicon-based aerogel powder prepared by microwave drying and its preparation method. Background Technology

[0002] Amorphous silicon-based aerogel powder, as a functional material, has significant application value in thermal management, electronic packaging insulation, and flame retardant protection. As one of the solid materials with the lowest known thermal conductivity, amorphous silicon-based aerogel powder possesses extremely high specific surface area and extremely low density, playing an irreplaceable role as a functional filler in polymer composites, plastic matrices, and coating systems. However, to achieve hydrophobicity and low density, hydrophobic modifiers and reinforcing fibers need to be introduced during the preparation of aerogel powder. The poor compatibility between hydrophobic components and hydrophilic silica sol systems leads to uneven dispersion and phase separation when directly blended, resulting in numerous skeletal defects and uneven performance after drying. It is difficult to simultaneously achieve low density and high structural integrity.

[0003] To alleviate this contradiction, existing technologies employ post-treatment impregnation and physical blending to introduce hydrophobic agents and reinforcing fibers into the aerogel framework. While this can locally improve performance, the process is complex, lacks uniformity, and fails to address the industry pain point of nanoporous structure collapse and failure during subsequent high-temperature thermal processing such as plastic extrusion and injection molding. Once the framework is damaged, the thermal insulation performance is significantly reduced. Therefore, there is an urgent need to develop a novel aerogel-based powder with uniformly dispersed hydrophobic components, a self-healing framework structure, and a tunable multi-level pore structure to meet the comprehensive requirements of the thermal management field for high-performance thermal insulation fillers.

[0004] To address the above problems, the present invention provides a solution. Summary of the Invention

[0005] The purpose of this invention is to provide an amorphous silicon-based aerogel powder prepared by microwave drying and its preparation method, which can solve the problems of poor compatibility between hydrophobic functional components and hydrophilic sols and the collapse and failure of aerogel nanoporous structures during thermal processing.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: an amorphous silicon-based aerogel powder prepared by microwave drying, comprising the following components by mass percentage: 28-30% tetraethyl orthosilicate, 23-25% anhydrous ethanol, 10-12% aqueous construct, 4-6% hexamethyldisilazane, 0.7-1% γ-mercaptopropyltriethoxysilane, 1-1.5% hydrogen peroxide solution, 0.3-0.5% acetic acid solution, 2-3% hydrochloric acid solution, 3-4% ammonia water, and 17-28% deionized water; Furthermore, the water-based construct composition comprises the following components by weight percentage: 19% fumed silica, 3% hexamethyldisilazane, 2% anhydrous ethanol, 21% chopped glass fiber, 2.4% acrylonitrile, 1.6% methyl methacrylate, 0.08% azobisisobutyronitrile, 3.5% isobutane, 1.5% nano silica, 1% sodium dodecyl sulfate, 15% SEBS-g-MAH, 10% naphthenic oil, 2% antioxidant 1010, 2% sodium hydroxide, 5.92% ethyl acetate, and 10% deionized water; Furthermore, the preparation method of the water-based construct composition includes the following steps: A1: Place fumed silica in a vacuum drying oven at a temperature of 110-130℃ and a vacuum of -0.08 to -0.10 MPa for 1.5-2.5 hours. After drying, transfer it to a reactor equipped with a reflux condenser, add anhydrous ethanol, set the stirring speed to 200-300 rpm, and stir for 12-18 minutes. Add hexamethyldisilazane while stirring, heat to 55-65℃, and stir for 3.5-4.5 hours. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with anhydrous ethanol. Then place the filter cake in a vacuum drying oven at a temperature of 75-85℃ and a vacuum of -0.08 to -0.10 MPa for 3.5-4.5 hours. Pass the filter cake through a 200-mesh sieve to obtain hydrophobic silica. A2: Acrylonitrile, methyl methacrylate, and azobisisobutyronitrile are added to ethyl acetate. The stirring speed is set to 180-220 rpm, and the mixture is heated to 65-75℃ under nitrogen protection. The mixture is stirred for 4.5-5.5 h to obtain a copolymer solution. The copolymer solution is heated to 42-48℃, and the stirring speed is set to 180-220 rpm. The mixture is stirred for 12-18 min to obtain a wall material solution. Isobutane is liquefied through a low-temperature condenser and kept in liquid state at -12 to -8℃. The wall material solution is transferred to a high-pressure emulsification kettle with jacket cooling. The temperature is set to -7 to -3℃, and the stirring speed is set to 450-550 rpm. Under stirring, the wall material solution is injected into the liquid isobutane at a rate of 0.25-0.35 kg / min using a metering pump. The mixture is stirred and emulsified for 25-35 min to obtain a primary emulsion. A3: Add nano-silica and sodium dodecyl sulfate to pure water, set the stirring speed to 350-450 rpm, and stir for 18-22 min to obtain a dispersion, wherein the mass ratio of nano-silica, sodium dodecyl sulfate and pure water is 1.5:1:20. Heat the primary emulsion to 22-28℃, and use a metering pump to inject the dispersion into the emulsion at a rate of 0.18-0.22 kg / min. Set the stirring speed to 550-650 rpm and stir for 12-18 min. Then heat to 62-68℃ and continue stirring for 3.5-4.5 h. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with deionized water. Place the filter cake in a vacuum drying oven, set the temperature to 42-48℃, the vacuum degree to -0.08 to -0.10 MPa, and dry for 7-9 h. Pass through a 200-mesh sieve to obtain thermally expanded capsules. A4: Add chopped glass fibers and thermal expansion capsules to a high-speed mixer, set the speed to 220-280 rpm, the mixing temperature to 22-28℃, and mix for 8-12 minutes. During the mixing process, use intermittent forward and reverse stirring, rotating forward for 1.5-2.5 minutes and then reverse for 1.5-2.5 minutes to obtain a multifunctional powder premix. Place naphthenic oil in a heating kettle with jacket heating and nitrogen protection, preheat to 115-125℃, add SEBS-g-MAH and antioxidant 1010, set the stirring speed to 180-220 rpm, and stir for 20-25 minutes to obtain a SEBS-g-MAH naphthenic oil solution. A5: Cool the SEBS-g-MAH naphthenic oil solution to 55-65℃, set the stirring speed to 180-220 rpm, and use a metering pump to inject the SEBS-g-MAH naphthenic oil solution into the multifunctional powder premix at a rate of 1-1.4 kg / min while stirring. The mixing temperature is 42-48℃. After the addition is complete, continue stirring for 30-40 min to obtain the oil-filled functional slurry. Add sodium hydroxide to 50% of the formula amount of deionized water, set the stirring speed to 220-280 rpm, and stir until completely dissolved to obtain a sodium hydroxide solution. Transfer the oil-filled functional slurry to a closed emulsification kettle with jacket heating, heat to 120-130℃, and use a metering pump to inject the sodium hydroxide solution into the oil-filled functional slurry at a rate of 0.35-0.45 kg / min. Set the emulsification kettle speed to 450-550 rpm and stir for 22-28 min to obtain the initial mixture. A6: Lower the temperature of the emulsification tank to 85-95℃, and inject 50% of the formula amount of preheated deionized water at 85-95℃ into the initial mixture at a rate of 0.55-0.65 kg / min using a metering pump. After injection, lower the temperature of the emulsification tank to 45-55℃, and continue stirring and maturing at 450-550 rpm for 25-35 min. Then, cool to room temperature through a plate heat exchanger, add hydrophobic silica, set the stirring speed to 250-350 rpm, and stir for 12-18 min. After stirring, pass through a 100-mesh sieve to obtain the water-based construct composition, which should be used within 48 hours. Furthermore, the specific surface area of ​​the fumed silica is 200 m². 2 / g, with a native particle size of 12nm; the chopped glass fiber has a length of 80um and a diameter of 6um; the SEBS-g-MAH has a styrene content of 20wt%, a maleic anhydride grafting rate of 1.5wt%, and a melt flow index of 8g / 10min measured under 230℃ and 5kg load conditions. Furthermore, a method for preparing amorphous silicon-based aerogel powder by microwave drying includes the following steps: S1: Add tetraethyl orthosilicate, 2 / 3 of the formula amount of anhydrous ethanol and 50% of the formula amount of deionized water to a reaction vessel, set the stirring speed to 300 rpm, add hydrochloric acid solution dropwise while stirring, and hydrolyze at 32℃ for 45 min to obtain silica sol. Add γ-mercaptopropyltriethoxysilane and 1 / 3 of the formula amount of anhydrous ethanol to a reaction vessel equipped with a reflux condenser, set the stirring speed to 250 rpm, introduce nitrogen protection, heat to 45℃, and stir for 12 min to obtain mercaptosilane solution. S2: Transfer the mercaptosilane solution to the reaction vessel, set the stirrer speed to 250 rpm, and use a constant flow pump to add hydrogen peroxide solution dropwise to the mercaptosilane solution at a rate of 0.15 kg / min. During the dropwise addition, control the reaction temperature to not exceed 55℃. After the dropwise addition is completed, raise the temperature to 60℃, keep the stirrer speed constant, and continue stirring for 3.5 h. After the reaction is completed, raise the temperature to 90℃, keep it at the temperature and stir for 60 min to decompose the residual hydrogen peroxide. Then add acetic acid solution, stir at 200 rpm for 12 min, and cool to room temperature to obtain the reaction solution. S3: Mix the reaction solution with the remaining amount of deionized water in the formula, set the stirrer speed to 250 rpm, stir for 5 min, add it to the silica sol after stirring, set the stirrer speed to 350 rpm, and continue stirring for 18 min to obtain a dynamic bond hybrid silica sol. Add the water-based building composition to the dynamic bond hybrid silica sol, set the stirrer speed to 450 rpm, and stir for 25 min. After stirring, set the ultrasonic power to 300 W and the ultrasonic frequency to 20 kHz, and ultrasonically disperse for 12 min. After ultrasonic dispersion, cool to room temperature, then set the stirrer speed to 450 rpm, and slowly add ammonia water dropwise while stirring. After the addition is complete, stop stirring and let the gel stand to obtain a dynamic bond hybrid composite wet gel. S4: Add anhydrous ethanol and pure water to the reactor and mix and stir at 200 rpm for 5 min to obtain an ethanol / water mixture, wherein the volume ratio of ethanol to pure water is 1:1. Add anhydrous ethanol and n-hexane to the reactor and mix and stir at 200 rpm for 5 min to obtain an ethanol / n-hexane mixture, wherein the volume ratio of anhydrous ethanol to n-hexane is 1:1. Preheat the ethanol / water mixture to 50℃. Then, add the dynamic bond hybrid composite wet gel to the preheated ethanol / water mixture and age for 14 h. After aging, transfer it to the ethanol / n-hexane mixture and continue aging for 7 h. After the continued aging, transfer it to n-hexane and age for a final 7 h. After the final aging, the displacement wet gel is obtained. S5: Hexamethyldisilazane was added to n-hexane to obtain a modified solution, wherein the mass ratio of hexamethyldisilazane to n-hexane was 1:25. The displacement wet gel was then immersed in the modified solution and soaked at room temperature for 2.5 hours. After soaking, the modified solution was drained, and the wet gel was transferred separately to a microwave drying device. A segmented program was set for microwave drying. The first stage temperature was 50℃, the microwave power was 200W, and the drying time was 30 minutes. The second stage temperature was 70℃, the microwave power was 350W, and the drying time was 25 minutes. The third stage temperature was 90℃, the microwave power was 500W, and the drying time was 15 minutes. The fourth stage temperature was 110℃, the microwave power was 600W, and the drying time was 10 minutes. After drying, a block aerogel was obtained. S6: The blocky aerogel is transferred to a jaw crusher and coarsely crushed into particles with a diameter of less than 5 mm. Then, it is finely crushed using an air jet mill at a crushing pressure of 0.7 MPa and a classifying speed of 4000 rpm. The aerogel base powder is obtained through multi-stage cyclone separation. The aerogel base powder is passed through a 200-mesh sieve to obtain amorphous silicon-based aerogel base powder prepared by microwave drying. Furthermore, the concentration of the acetic acid solution is 0.5 mol / L; the concentration of the hydrochloric acid solution is 0.1 mol / L; the concentration of the ammonia solution is 0.5 mol / L; and the concentration of the hydrogen peroxide solution is 30 wt%. In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows: 1. This invention pre-integrates hydrophobic silica, chopped glass fibers, and thermally expandable capsules into a SEBS-g-MAH / cycloalkane oil carrier by using a phase inversion method to pre-prepare a water-based construct composition. This systematically solves the key problems of poor compatibility between hydrophobic functional components and hydrophilic silica sol, and premature failure of thermally expandable capsules during gelation. At the same time, by using segmented microwave drying and in-situ pore-forming of thermally expandable microspheres in synergy, a multi-level porous structure with interconnected nanopores and micron cavities is constructed in one step in the aerogel framework, achieving a synergistic effect of low density, high specific surface area, and durable hydrophobicity. 2: This invention introduces dynamic disulfide bonds into the aerogel framework, co-hydrolyzes and polycondenses γ-mercaptopropyltriethoxysilane with tetraethyl orthosilicate, and in-situ embeds reversible covalent bonds in the silica network, endowing the aerogel-based powder with the ability to self-repair its microstructure during multiple thermal processing and recycling. This effectively solves the industry pain point of nanoporous structure collapse and failure of traditional aerogel powder in subsequent high-temperature and high-shear processing such as plastic extrusion and injection molding, and greatly improves the processing adaptability and service life of aerogel-based powder as a functional filler. 3: This invention utilizes the latent thermal triggering characteristics of thermal expansion capsules and the precise temperature control of microwave segmented drying to control the temperature below the initial expansion temperature of thermal expansion capsules during the microwave drying stage of aerogel preparation in order to preserve their latent activity. When the base powder encounters high temperatures in the application scenario, the thermal expansion capsules expand a second time to trigger an active thermal insulation response, providing a brand-new solution for aerogel base powder to have both inherent thermal insulation and high-temperature triggered secondary thermal insulation functions. Detailed Implementation

[0007] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.

[0008] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0009] Example 1 1. Place 1.9 kg of fumed silica in a vacuum drying oven, set the temperature to 110℃ and the vacuum degree to -0.08 MPa, and dry for 1.5 h. After drying, transfer it to a reaction vessel equipped with a reflux condenser, add 0.2 kg of anhydrous ethanol, set the stirring speed to 200 rpm, and stir and disperse for 12 min. Add 0.3 kg of hexamethyldisilazane while stirring, heat to 55℃, and stir and react for 3.5 h. After the reaction is complete, cool to room temperature, filter using a vacuum filtration device, wash the filter cake three times with anhydrous ethanol, and then place the filter cake in a vacuum drying oven, set the temperature to 75℃ and the vacuum degree to -0.08 MPa, and dry for 3.5 h. Pass through a 200-mesh sieve to obtain 1.82 kg of hydrophobic silica. 2: Add 0.24 kg acrylonitrile, 0.16 kg methyl methacrylate and 0.008 kg azobisisobutyronitrile to 0.592 kg ethyl acetate. Set the stirring speed to 180 rpm and heat to 65°C under nitrogen protection. Stir and react for 4.5 h to obtain 0.96 kg copolymer solution. Heat the copolymer solution to 42°C and stir at 180 rpm for 12 min to obtain 0.95 kg wall material solution. Liquefy 0.35 kg isobutane through a low-temperature condenser and keep it in liquid state at -8°C for later use. Transfer the 0.95 kg wall material solution to a high-pressure emulsification kettle with jacket cooling. Set the temperature to -3°C and the stirring speed to 450 rpm. While stirring, use a metering pump to inject the wall material solution into the liquid isobutane at a rate of 0.25 kg / min. Stir and emulsify for 25 min to obtain 1.24 kg primary emulsion. 3: Add 0.15 kg of nano-silica and 0.1 kg of sodium dodecyl sulfate to 2 kg of pure water. Set the stirring speed to 350 rpm and stir for 18 min to obtain 2.19 kg of dispersion. Heat 1.24 kg of primary emulsion to 22 °C and use a metering pump to inject 2.19 kg of dispersion into the emulsion at a rate of 0.18 kg / min. Set the stirring speed to 550 rpm and stir for 12 min. Then raise the temperature to 62 °C and continue stirring for 3.5 h. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with deionized water. Place the filter cake in a vacuum drying oven at 42 °C and a vacuum degree of -0.08 MPa for 7 h and pass it through a 200-mesh sieve to obtain 0.43 kg of thermally expanded capsules. 4: Add 2.1 kg of chopped glass fiber and 0.43 kg of thermal expansion capsules to a high-speed mixer, set the speed to 220 rpm, the mixing temperature to 22℃, and mix for 8 minutes. During the mixing process, use intermittent forward and reverse stirring, rotating forward for 1.5 minutes and then reverse for 1.5 minutes in a cycle to obtain 2.48 kg of multifunctional powder premix. Place 1 kg of naphthenic oil in a heating kettle with jacket heating and nitrogen protection, preheat to 115℃, add 1.5 kg of SEBS-g-MAH and 0.2 kg of antioxidant 1010, set the stirring speed to 180 rpm, and stir for 20 minutes to obtain 2.63 kg of SEBS-g-MAH naphthenic oil solution. 5: Cool 2.63 kg of SEBS-g-MAH naphthenic oil solution to 55°C, set the stirring speed to 180 rpm, and use a metering pump to inject the SEBS-g-MAH naphthenic oil solution into 2.48 kg of multifunctional powder premix at a rate of 1 kg / min while stirring. The mixing temperature is 42°C. After the addition is complete, continue stirring for 30 min to obtain 4.98 kg of oil-filled functional slurry. Add 0.2 kg of sodium hydroxide to 0.5 kg of deionized water, set the stirring speed to 220 rpm, and stir until completely dissolved to obtain 0.68 kg of sodium hydroxide solution. Transfer 4.98 kg of oil-filled functional slurry to a closed emulsification kettle with jacket heating, heat to 120°C, and use a metering pump to inject 0.68 kg of sodium hydroxide solution into the oil-filled functional slurry at a rate of 0.35 kg / min. Set the emulsification kettle speed to 450 rpm and stir for 22 min to obtain 5.52 kg of initial mixture. 6: Lower the temperature of the emulsification tank to 85°C, and inject 0.5 kg of preheated deionized water (85°C) into 5.52 kg of initial mixture at a rate of 0.55 kg / min using a metering pump. After injection, lower the temperature of the emulsification tank to 45°C and continue stirring at 450 rpm for 25 min. Then, cool it to room temperature using a plate heat exchanger, add 1.82 kg of hydrophobic silica, set the stirring speed to 250 rpm, and stir for 12 min. After stirring, pass the mixture through a 100-mesh sieve to obtain 7.58 kg of the water-based construct composition prepared in Example 1, which should be used within 48 hours. Example 2 1. Place 1.9 kg of fumed silica in a vacuum drying oven, set the temperature to 130℃ and the vacuum degree to -0.10 MPa, and dry for 2.5 h. After drying, transfer it to a reaction vessel equipped with a reflux condenser, add 0.2 kg of anhydrous ethanol, set the stirring speed to 300 rpm, and stir and disperse for 18 min. Add 0.3 kg of hexamethyldisilazane while stirring, heat to 65℃, and stir and react for 4.5 h. After the reaction is complete, cool to room temperature, filter using a vacuum filtration device, wash the filter cake three times with anhydrous ethanol, and then place the filter cake in a vacuum drying oven, set the temperature to 85℃ and the vacuum degree to -0.10 MPa, and dry for 4.5 h. Pass through a 200-mesh sieve to obtain 1.8 kg of hydrophobic silica. 2: Add 0.24 kg acrylonitrile, 0.16 kg methyl methacrylate and 0.008 kg azobisisobutyronitrile to 0.592 kg ethyl acetate. Set the stirring speed to 220 rpm and heat to 75 °C under nitrogen protection. Stir and react for 5.5 h to obtain 0.95 kg copolymer solution. Heat the copolymer solution to 48 °C and stir at 220 rpm for 18 min to obtain 0.94 kg wall material solution. Liquefy 0.35 kg isobutane through a low-temperature condenser and keep it in liquid state at -12 °C for later use. Transfer the 0.94 kg wall material solution to a high-pressure emulsification kettle with jacket cooling. Set the temperature to -7 °C and the stirring speed to 550 rpm. While stirring, use a metering pump to inject the wall material solution into the liquid isobutane at a rate of 0.35 kg / min. Stir and emulsify for 35 min to obtain 1.22 kg primary emulsion. 3: Add 0.15 kg of nano-silica and 0.1 kg of sodium dodecyl sulfate to 2 kg of pure water. Set the stirring speed to 450 rpm and stir for 22 min to obtain 2.18 kg of dispersion. Heat 1.22 kg of primary emulsion to 28 °C and inject 2.18 kg of dispersion into the emulsion at a rate of 0.22 kg / min using a metering pump. Set the stirring speed to 650 rpm and stir for 18 min. Then heat to 68 °C and continue stirring for 4.5 h. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with deionized water. Place the filter cake in a vacuum drying oven at 48 °C and a vacuum degree of -0.10 MPa for 9 h and pass through a 200-mesh sieve to obtain 0.42 kg of thermally expanded capsules. 4: Add 2.1 kg of chopped glass fiber and 0.42 kg of thermal expansion capsules to a high-speed mixer, set the speed to 280 rpm, the mixing temperature to 28℃, and mix for 12 min. During the mixing process, use intermittent forward and reverse stirring, rotating forward for 2.5 min and then reverse for 2.5 min, repeating the cycle to obtain 2.46 kg of multifunctional powder premix. Place 1 kg of naphthenic oil in a heating kettle with jacket heating and nitrogen protection, preheat to 125℃, add 1.5 kg of SEBS-g-MAH and 0.2 kg of antioxidant 1010, set the stirring speed to 220 rpm, and stir for 25 min to obtain 2.61 kg of SEBS-g-MAH naphthenic oil solution. 5: Cool 2.61 kg of SEBS-g-MAH naphthenic oil solution to 65°C, set the stirring speed to 220 rpm, and use a metering pump to inject the SEBS-g-MAH naphthenic oil solution into 2.46 kg of multifunctional powder premix at a rate of 1.4 kg / min while stirring. The mixing temperature is 48°C. After the addition is complete, continue stirring for 40 min to obtain 4.94 kg of oil-filled functional slurry. Add 0.2 kg of sodium hydroxide to 0.5 kg of deionized water, set the stirring speed to 280 rpm, and stir until completely dissolved to obtain 0.67 kg of sodium hydroxide solution. Transfer 4.94 kg of oil-filled functional slurry to a closed emulsification kettle with jacket heating, heat to 130°C, and use a metering pump to inject 0.67 kg of sodium hydroxide solution into the oil-filled functional slurry at a rate of 0.45 kg / min. Set the emulsification kettle speed to 550 rpm and stir for 28 min to obtain 5.46 kg of initial mixture. 6: Lower the temperature of the emulsification tank to 95°C, and inject 0.5 kg of preheated deionized water (preheated to 95°C) into 5.46 kg of initial mixture at a rate of 0.65 kg / min using a metering pump. After injection, lower the temperature of the emulsification tank to 55°C and continue stirring at 550 rpm for 35 min. Then, cool it to room temperature using a plate heat exchanger, add 1.80 kg of hydrophobic silica, set the stirring speed to 350 rpm, and stir for 18 min. After stirring, pass the mixture through a 100-mesh sieve to obtain 7.48 kg of the water-based construct composition prepared in Example 2, which should be used within 48 hours. Example 3 1. Add 28 kg of tetraethyl orthosilicate, 15.33 kg of anhydrous ethanol and 14 kg of deionized water to a reaction vessel. Set the stirring speed to 300 rpm. Add 2 kg of hydrochloric acid solution dropwise while stirring. Hydrolyze at 32 °C for 45 min to obtain 59.03 kg of silica sol. Add 0.7 kg of γ-mercaptopropyltriethoxysilane and 7.67 kg of anhydrous ethanol to a reaction vessel equipped with a reflux condenser. Set the stirring speed to 250 rpm. Purge with nitrogen protection and heat to 45 °C. Stir for 12 min to obtain 8.28 kg of mercaptosilane solution. 2: Transfer 8.28 kg of mercaptosilane solution to a reaction vessel. Set the stirrer speed to 250 rpm and use a constant flow pump to add 1 kg of hydrogen peroxide solution dropwise to the mercaptosilane solution at a rate of 0.15 kg / min. During the dropwise addition, control the reaction temperature to not exceed 55℃. After the dropwise addition is completed, raise the temperature to 60℃, keep the stirrer speed constant, and continue stirring for 3.5 h. After the reaction is completed, raise the temperature to 90℃, keep it at this temperature and stir for 60 min to decompose the residual hydrogen peroxide. Then add 0.3 kg of acetic acid solution, stir at 200 rpm for 12 min, and cool to room temperature to obtain 9.35 kg of reaction solution. 3: Mix 9.35 kg of reaction solution with 14 kg of deionized water, set the stirrer speed to 250 rpm, and stir for 5 min to obtain 23.16 kg of diluted reaction solution. After stirring, add 23.16 kg of diluted reaction solution to 59.03 kg of silica sol, set the stirrer speed to 350 rpm, and continue stirring for 18 min to obtain 81.68 kg of dynamic bond hybrid silica sol. Add 10 kg of the water-based construct composition prepared in Example 1 to the dynamic bond hybrid silica sol, set the stirrer speed to 450 rpm, and stir for 25 min. After stirring, set the ultrasonic power to 300 W and the ultrasonic frequency to 20 kHz, and ultrasonically disperse for 12 min. Then set the stirrer speed to 450 rpm and slowly add 3 kg of ammonia water dropwise while stirring. After the addition is complete, stop stirring and let the gel stand to obtain 93.85 kg of dynamic bond hybrid composite wet gel. 4: Add 200L of anhydrous ethanol and 200L of pure water to the reactor and mix at 200rpm for 5min to obtain an ethanol / water mixture. Add 200L of anhydrous ethanol and 200L of n-hexane to the reactor and mix at 200rpm for 5min to obtain an ethanol / n-hexane mixture. Preheat the ethanol / water mixture to 50℃. Then, add 93.85kg of dynamic bond hybrid composite wet gel to the preheated ethanol / water mixture and age for 14h. After aging, transfer to the ethanol / n-hexane mixture and continue aging for 7h. After further aging, transfer to n-hexane and age for a final 7h. After final aging, 92.85kg of displacement wet gel is obtained. 5: Add 4 kg of hexamethyldisilazane to 100 kg of n-hexane to obtain 104 kg of modified solution. Then, immerse 92.85 kg of displacement wet gel in the modified solution and soak at room temperature for 2.5 h. After soaking, drain the modified solution and transfer the wet gel separately to a microwave drying device. Set a segmented program for microwave drying. The first stage temperature is 50℃, microwave power is 200 W, and drying time is 30 min. The second stage temperature is 70℃, microwave power is 350 W, and drying time is 25 min. The third stage temperature is 90℃, microwave power is 500 W, and drying time is 15 min. The fourth stage temperature is 110℃, microwave power is 600 W, and drying time is 10 min. After drying, 8.52 kg of block aerogel is obtained. 6: 8.52 kg of blocky aerogel was transferred to a jaw crusher and coarsely crushed into particles with a diameter of less than 5 mm. Then, it was finely crushed using an air jet mill at a crushing pressure of 0.7 MPa and a classifying speed of 4000 rpm. The aerogel base powder was obtained by multi-stage cyclone separation. The aerogel base powder was passed through a 200-mesh sieve to obtain 7.85 kg of the amorphous silicon-based aerogel base powder prepared by microwave drying in Example 3. Example 4 1. Add 30 kg of tetraethyl orthosilicate, 16.67 kg of anhydrous ethanol and 8.5 kg of deionized water to a reaction vessel. Set the stirring speed to 300 rpm. Add 3 kg of hydrochloric acid solution dropwise while stirring. Hydrolyze at 32 °C for 45 min to obtain 57.82 kg of silica sol. Add 1 kg of γ-mercaptopropyltriethoxysilane and 8.33 kg of anhydrous ethanol to a reaction vessel equipped with a reflux condenser. Set the stirring speed to 250 rpm. Purge with nitrogen protection and heat to 45 °C. Stir for 12 min to obtain 9.25 kg of mercaptosilane solution. 2: Transfer 9.25 kg of mercaptosilane solution to a reaction vessel. Set the stirrer speed to 250 rpm and use a constant flow pump to add 1.5 kg of hydrogen peroxide solution dropwise to the mercaptosilane solution at a rate of 0.15 kg / min. During the dropwise addition, control the reaction temperature to not exceed 55℃. After the dropwise addition is completed, raise the temperature to 60℃, keep the stirrer speed constant, and continue stirring for 3.5 h. After the reaction is completed, raise the temperature to 90℃, keep it at this temperature and stir for 60 min to decompose the residual hydrogen peroxide. Then add 0.5 kg of acetic acid solution, stir at 200 rpm for 12 min, and cool to room temperature to obtain 10.98 kg of reaction solution. 3: Mix 10.98 kg of reaction solution with 8.5 kg of deionized water, set the stirrer speed to 250 rpm, and stir for 5 min to obtain 19.35 kg of diluted reaction solution. After stirring, add 19.35 kg of diluted reaction solution to 57.82 kg of silica sol, set the stirrer speed to 350 rpm, and continue stirring for 18 min to obtain 76.85 kg of dynamic bond hybrid silica sol. Add 12 kg of the water-based construct composition prepared in Example 2 to 76.85 kg of dynamic bond hybrid silica sol, set the stirrer speed to 450 rpm, and stir for 25 min. After stirring, set the ultrasonic power to 300 W and the ultrasonic frequency to 20 kHz, and ultrasonically disperse for 12 min. Then set the stirrer speed to 450 rpm and slowly add 4 kg of ammonia water dropwise while stirring. After the addition is complete, stop stirring and let the gel stand to obtain 92.05 kg of dynamic bond hybrid composite wet gel. 4: Add 200L of anhydrous ethanol and 200L of pure water to the reactor and mix at 200rpm for 5min to obtain an ethanol / water mixture. Add 200L of anhydrous ethanol and 200L of n-hexane to the reactor and mix at 200rpm for 5min to obtain an ethanol / n-hexane mixture. Preheat the ethanol / water mixture to 50℃. Then, add 92.05kg of dynamic bond hybrid composite wet gel to the preheated ethanol / water mixture and age for 14h. After aging, transfer to the ethanol / n-hexane mixture and continue aging for 7h. After further aging, transfer to n-hexane and age for a final 7h. After final aging, 90.28kg of displacement wet gel is obtained. 5: 6 kg of hexamethyldisilazane was added to 150 kg of n-hexane to obtain 156 kg of modified solution. Then, 90.28 kg of displacement wet gel was immersed in the modified solution and soaked at room temperature for 2.5 h. After soaking, the modified solution was drained, and the wet gel was transferred separately to a microwave drying device. A segmented program was set for microwave drying. The first stage temperature was 50℃, microwave power was 200 W, and drying time was 30 min. The second stage temperature was 70℃, microwave power was 350 W, and drying time was 25 min. The third stage temperature was 90℃, microwave power was 500 W, and drying time was 15 min. The fourth stage temperature was 110℃, microwave power was 600 W, and drying time was 10 min. After drying, 9.45 kg of block aerogel was obtained. 6: 9.45 kg of blocky aerogel was transferred to a jaw crusher and coarsely crushed into particles with a diameter of less than 5 mm. Then, it was finely crushed using an air jet mill at a crushing pressure of 0.7 MPa and a classifying speed of 4000 rpm. The aerogel base powder was obtained by multi-stage cyclone separation. The aerogel base powder was passed through a 200-mesh sieve to obtain 8.72 kg of the amorphous silicon-based aerogel base powder prepared by microwave drying in Example 4. Comparative Example 1 The difference between this comparative example and Example 3 is that the water-based construct composition prepared in Example 1 is not used. Instead, the functional components are prepared separately and then directly added to the dynamically bonded hybrid silica sol. The other components and processes remain unchanged. The specific preparation method is as follows: 1. Place 1.9 kg of fumed silica in a vacuum drying oven, set the temperature to 120℃ and the vacuum degree to -0.09 MPa, and dry for 2 h. After drying, transfer it to a reaction vessel equipped with a reflux condenser, add 0.2 kg of anhydrous ethanol, set the stirring speed to 250 rpm, and stir and disperse for 15 min. Add 0.3 kg of hexamethyldisilazane while stirring, heat to 60℃, and stir and react for 4 h. After the reaction is complete, cool to room temperature, filter using a vacuum filtration device, wash the filter cake 3 times with anhydrous ethanol, and then place the filter cake in a vacuum drying oven, set the temperature to 80℃ and the vacuum degree to -0.09 MPa, and dry for 4 h. Pass through a 200-mesh sieve to obtain 1.82 kg of hydrophobic silica. 2: Add 0.24 kg acrylonitrile, 0.16 kg methyl methacrylate and 0.008 kg azobisisobutyronitrile to 0.592 kg ethyl acetate. Set the stirring speed to 200 rpm and heat to 70 °C under nitrogen protection. Stir for 5 h to obtain 0.96 kg copolymer solution. Heat the copolymer solution to 45 °C and stir at 200 rpm for 15 min to obtain 0.95 kg wall material solution. Liquefy 0.35 kg isobutane through a low-temperature condenser and keep it in liquid state at -10 °C for later use. Transfer the 0.95 kg wall material solution to a high-pressure emulsification kettle with jacket cooling. Set the temperature to -5 °C and the stirring speed to 500 rpm. While stirring, use a metering pump to inject the wall material solution into the liquid isobutane at a rate of 0.3 kg / min. Stir and emulsify for 30 min to obtain 1.24 kg primary emulsion. 3: Add 0.15 kg of nano-silica and 0.1 kg of sodium dodecyl sulfate to 2 kg of pure water. Set the stirring speed to 400 rpm and stir for 20 min to obtain 2.19 kg of dispersion. Heat 1.24 kg of primary emulsion to 25 °C and use a metering pump to inject 2.19 kg of dispersion into the emulsion at a rate of 0.2 kg / min. Set the stirring speed to 600 rpm and stir for 15 min. Then raise the temperature to 65 °C and continue stirring for 4 h. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with deionized water. Place the filter cake in a vacuum drying oven at 45 °C and a vacuum degree of -0.09 MPa for 8 h and pass it through a 200-mesh sieve to obtain 0.43 kg of thermally expanded capsules. 4: Place 1 kg of naphthenic oil in a heated vessel with jacket heating and nitrogen protection, preheat to 120°C, add 1.5 kg of SEBS-g-MAH and 0.2 kg of antioxidant 1010, set the stirring speed to 200 rpm, and stir for 22 min to obtain 2.63 kg of SEBS-g-MAH naphthenic oil solution. 5: Add 28 kg of tetraethyl orthosilicate, 15.33 kg of anhydrous ethanol and 14 kg of deionized water to a reaction vessel. Set the stirring speed to 300 rpm. Add 2 kg of hydrochloric acid solution dropwise while stirring. Hydrolyze at 32 °C for 45 min to obtain 59.03 kg of silica sol. Add 0.7 kg of γ-mercaptopropyltriethoxysilane and 7.67 kg of anhydrous ethanol to a reaction vessel equipped with a reflux condenser. Set the stirring speed to 250 rpm. Purge with nitrogen for protection. Heat to 45 °C and stir for 12 min to obtain 8.28 kg of mercaptosilane solution. 6: Transfer 8.28 kg of mercaptosilane solution to a reaction vessel. Set the stirrer speed to 250 rpm and use a constant flow pump to add 1 kg of hydrogen peroxide solution dropwise to the mercaptosilane solution at a rate of 0.15 kg / min. During the dropwise addition, control the reaction temperature to not exceed 55℃. After the dropwise addition is completed, raise the temperature to 60℃, keep the stirrer speed constant, and continue stirring for 3.5 h. After the reaction is completed, raise the temperature to 90℃, keep it at this temperature and stir for 60 min to decompose the residual hydrogen peroxide. Then add 0.3 kg of acetic acid solution, stir at 200 rpm for 12 min, and cool to room temperature to obtain 9.35 kg of reaction solution. 7: Mix 9.35 kg of reaction solution with 14 kg of deionized water, set the stirrer speed to 250 rpm, and stir for 5 min to obtain 23.35 kg of diluted reaction solution. After stirring, add 23.35 kg of diluted reaction solution to 59.03 kg of silica sol, set the stirrer speed to 350 rpm, and continue stirring for 18 min to obtain 82.07 kg of dynamically bonded hybrid silica sol. Add 1.82 kg of hydrophobic silica, 2.1 kg of chopped glass fiber, 0.43 kg of thermally expanded capsules, and 2.6 kg of other components. 3 kg of SEBS-g-MAH naphthenic oil solution and 0.2 kg of sodium hydroxide were added sequentially to 82.07 kg of dynamic bond hybrid silica sol. The stirrer was set to 450 rpm and stirred for 25 min. After stirring, the ultrasonic power was set to 300 W and the ultrasonic frequency was set to 20 kHz and ultrasonic dispersion was performed for 12 min. Then, the stirrer was set to 450 rpm and 3 kg of ammonia water was slowly added dropwise while stirring. After the addition was completed, stirring was stopped and the gel was allowed to stand to obtain 91.85 kg of dynamic bond hybrid composite wet gel. 8: Add anhydrous ethanol and pure water to the reactor and mix and stir at 200 rpm for 5 min to obtain an ethanol / water mixture, wherein the volume ratio of ethanol to pure water is 1:1. Add anhydrous ethanol and n-hexane to the reactor and mix and stir at 200 rpm for 5 min to obtain an ethanol / n-hexane mixture, wherein the volume ratio of anhydrous ethanol to n-hexane is 1:1. Preheat the ethanol / water mixture to 50℃, and then add 91.85 kg of dynamic bond hybrid composite wet gel to the preheated ethanol / water mixture for aging for 14 h. After aging, transfer to the ethanol / n-hexane mixture for further aging for 7 h. After further aging, transfer to n-hexane for final aging for 7 h. After final aging, 90.02 kg of displacement wet gel is obtained. 9: Add 4 kg of hexamethyldisilazane to 100 kg of n-hexane to obtain 104 kg of modified solution. Then, immerse 90.02 kg of displacement wet gel in the modified solution and soak at room temperature for 2.5 h. After soaking, drain the modified solution and transfer the wet gel separately to a microwave drying device. Set a segmented program for microwave drying. The first stage temperature is 50℃, microwave power is 200 W, and drying time is 30 min. The second stage temperature is 70℃, microwave power is 350 W, and drying time is 25 min. The third stage temperature is 90℃, microwave power is 500 W, and drying time is 15 min. The fourth stage temperature is 110℃, microwave power is 600 W, and drying time is 10 min. After drying, 7.52 kg of block aerogel is obtained. 10: 7.52 kg of blocky aerogel was transferred to a jaw crusher and coarsely crushed into particles with a diameter of less than 5 mm. Then, it was finely crushed using an air jet mill at a crushing pressure of 0.7 MPa and a classifying speed of 4000 rpm. The aerogel base powder was obtained by multi-stage cyclone separation. The aerogel base powder was passed through a 200-mesh sieve to obtain 6.85 kg of microwave-dried amorphous silicon-based aerogel base powder prepared in Comparative Example 1. Comparative Example 2 The difference between this comparative example and Example 3 is that γ-mercaptopropyltriethoxysilane, hydrogen peroxide solution and acetic acid solution are not added, dynamic disulfide bond hybridization is not performed, and the corresponding components are replaced by tetraethyl orthosilicate, anhydrous ethanol and deionized water in equal mass, while the other components and processes remain unchanged. The specific preparation method is as follows: 1: Add 28.7 kg of tetraethyl orthosilicate, 16.05 kg of anhydrous ethanol and 14.3 kg of deionized water to a reaction vessel, set the stirring speed to 300 rpm, add 2 kg of hydrochloric acid solution dropwise while stirring, and hydrolyze at 32 °C for 45 min to obtain 60.75 kg of silica sol. 2: Add 21.67 kg of deionized water to 60.75 kg of silica sol, set the stirrer speed to 350 rpm, and continue stirring for 18 min to obtain 82.42 kg of silica sol dilution. Add 10 kg of the water-based construct composition prepared in Example 1 to the 82.42 kg silica sol dilution, set the stirrer speed to 450 rpm, and stir for 25 min. After stirring, set the ultrasonic power to 300 W and the ultrasonic frequency to 20 kHz, and ultrasonically disperse for 12 min. Then set the stirrer speed to 450 rpm and slowly add 3 kg of ammonia water dropwise while stirring. After the addition is complete, stop stirring and let the gel stand to obtain 94.95 kg of composite wet gel. 3: Add 200L of anhydrous ethanol and 200L of pure water to the reactor and mix at 200rpm for 5min to obtain an ethanol / water mixture. Add 200L of anhydrous ethanol and 200L of n-hexane to the reactor and mix at 200rpm for 5min to obtain an ethanol / n-hexane mixture. Preheat the ethanol / water mixture to 50℃. Then, add 94.95kg of composite wet gel to the preheated ethanol / water mixture and age for 14h. After aging, transfer to the ethanol / n-hexane mixture and continue aging for 7h. After the continued aging, transfer to n-hexane and age for a final 7h. After the final aging, 93.18kg of displacement wet gel is obtained. 4: Add 4 kg of hexamethyldisilazane to 100 kg of n-hexane to obtain 104 kg of modified solution. Then, immerse 93.18 kg of displacement wet gel in the modified solution and soak at room temperature for 2.5 h. After soaking, drain the modified solution and transfer the wet gel separately to a microwave drying device. Set a segmented program for microwave drying. The first stage temperature is 50℃, microwave power is 200 W, and drying time is 30 min. The second stage temperature is 70℃, microwave power is 350 W, and drying time is 25 min. The third stage temperature is 90℃, microwave power is 500 W, and drying time is 15 min. The fourth stage temperature is 110℃, microwave power is 600 W, and drying time is 10 min. After drying, 8.52 kg of block aerogel is obtained. 5: 8.52 kg of blocky aerogel was transferred to a jaw crusher and coarsely crushed into particles with a diameter of less than 5 mm. Then, it was finely crushed using an air jet mill at a crushing pressure of 0.7 MPa and a classifying speed of 4000 rpm. The aerogel base powder was obtained by multi-stage cyclone separation. The aerogel base powder was passed through a 200-mesh sieve to obtain 7.82 kg of microwave-dried amorphous silicon-based aerogel base powder prepared in Comparative Example 2. Basic performance test The microwave-dried amorphous silicon-based aerogel powders prepared in Examples 3, 4, Comparative Example 1 and Comparative Example 2 were subjected to basic physical property tests. Apparent density was determined according to GB / T 21354-2008 "Determination of tapped density and loose density of powder products"; specific surface area was determined according to GB / T 19587-2017 "Determination of specific surface area of ​​solid substances by gas adsorption BET method"; water contact angle was determined according to GB / T 30693-2014 "Measurement of water contact angle of plastic film"; each group of samples was tested in parallel three times, the average value was taken, and the test results were recorded. Table 1. Basic Performance Test Results ; Analysis of Table 1 shows that the apparent densities of Examples 3 and 4 are 0.12 g / cm³. 3 and 0.10 g / cm 3 The specific surface area reached 685m². 2 / g and 752m 2 / g, with water contact angles of 148° and 151° respectively, demonstrating that the aerogel-based powder prepared by this invention has low density, high specific surface area and excellent hydrophobic properties; The apparent density of Example 4 is lower than that of Example 3, while the specific surface area is higher. The reason for this is that the amount of water-based building composition and tetraethyl orthosilicate in Example 4 is at the upper limit of the formulation, the content of thermally expandable capsules and hydrophobic silica is higher, the microsphere expansion and pore-forming effect is stronger, and the hydrophobic micro-regions in the framework are more densely distributed. The apparent density of Comparative Example 1 is 0.18 g / cm³. 3 Compared to Example 3, the surface area increased by 50%, with a specific surface area of ​​only 423 m². 2 / g, a decrease of 38.2% compared to Example 3, and the water contact angle decreased to 132°, demonstrating that when the functional components are directly added to the silica sol without preparing a water-based building block composition, the hydrophobic silica and thermally expandable capsules are unevenly dispersed in the hydrophilic system, the thermally expandable capsules partially agglomerate, resulting in poor pore-forming effect, and the hydrophobic silica fails to effectively embed into the framework, resulting in a decrease in hydrophobic properties. The apparent density and specific surface area of ​​Comparative Example 2 are similar to those of Example 3, and the water contact angle is 146°, which is comparable to that of Example 3, indicating that the presence or absence of dynamic disulfide bonds has little effect on the basic physical properties.

[0010] Self-repair performance test The microwave-dried amorphous silicon-based aerogel powders prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were added to a thermoplastic polymer matrix at an addition amount of 10 wt%. The mixtures were melt-blended and extruded into granules in a twin-screw extruder at an extrusion temperature of 160°C and a screw speed of 200 rpm. The resulting granules were injection molded into standard tensile test strips. The strips were then re-crushed at 180°C and extruded again, undergoing a total of three heat treatment recycling cycles. The tensile strength and elongation at break of the strips were tested after each cycle according to GB / T 1040.2-2006 "Determination of tensile properties of plastics - Part 2: Test conditions for molding and extruding plastics". Each group of samples was tested in triplicate, and the average value was recorded. Table 2. Self-healing performance test results ; As shown in Table 2, the tensile strength retention rates of Examples 3 and 4 after three heat treatments and recyclings were 94.1% and 94.8%, respectively. This proves that the aerogel-based powder containing dynamic disulfide bonds prepared by the present invention can reversibly break and recombine disulfide bonds during high-temperature heat treatment, thus repairing the microstructure of the aerogel skeleton and making the nanoporous structure less prone to collapse, thereby endowing the composite material with excellent multiple recycling performance retention capabilities. The strength retention rate of Example 4 is slightly higher than that of Example 3. The reason is that the amount of tetraethyl orthosilicate used in Example 4 is higher, the disulfide bond grafting density in the skeleton is greater, and the self-healing efficiency is higher. The strength retention rate of Comparative Example 1 after three recycling cycles was only 66.3%, which was 27.8 percentage points lower than that of Example 3. The reason for this was that the hydrophobic silica and thermally expandable capsules in Comparative Example 1 were not evenly dispersed, and the aerogel powder had a large number of defects. During multiple thermal processing, the defects expanded, leading to accelerated performance degradation. Comparative Example 2 showed a strength retention rate of only 66.5% after three recycling cycles, a decrease of 27.6 percentage points compared to Example 3. This demonstrates that the nanoporous structure of the aerogel framework without dynamic disulfide bonds gradually collapses during repeated thermal processing and cannot achieve self-repair, fully verifying the key role of dynamic disulfide bonds in maintaining performance after multiple recycling cycles.

[0011] Thermal trigger response performance test The microwave-dried amorphous silicon-based aerogel powders prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were placed in a muffle furnace and heated from room temperature to 200°C at a heating rate of 5°C / min. The volume change of the samples during the heating process was recorded, and the expansion rate in the thickness direction of the samples was monitored using a thermomechanical analyzer (TMA). Each group of samples was tested in parallel three times, and the average value was taken and the test results were recorded. Table 3. Test results of thermal trigger response performance ; Analysis of Table 3 shows that significant volume expansion began to occur in Examples 3 and 4 at 165°C, and the volume expansion rates reached 35.6% and 42.8% respectively at 200°C. This proves that the thermal expansion capsules in the aerogel base powder prepared by the present invention undergo secondary expansion under high temperature triggering, giving the base powder active thermal response capability. The expansion rate of Example 4 was higher than that of Example 3. The reason for this is that the amount of water-based construct composition used in Example 4 was the upper limit of the formulation, and the content of thermally expandable capsules was higher, resulting in a stronger expansion driving force. Comparative Example 1 showed an expansion rate of 5.6% at 120°C, which was higher than 2.5% in Example 3. However, the expansion rates at 165°C and 200°C were only 8.2% and 12.5%, respectively, which were 55.7% and 64.9% lower than in Example 3. The reason for this was that the thermally expandable capsules in Comparative Example 1 were not protected by the water-based construct composition and partially expanded or ruptured during the early gelation process, resulting in a reduction in the number of effectively expandable capsules in the high-temperature range and a significant decrease in the thermal trigger response capability. The expansion rate of Comparative Example 2 is comparable to that of Example 3, indicating that the presence or absence of dynamic disulfide bonds has little effect on the thermally triggered response performance. The thermally triggered response mainly depends on the content and integrity of the thermally expanded capsule.

[0012] Thermal conductivity test The microwave-dried amorphous silicon-based aerogel powders prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were tested for thermal conductivity according to GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method". The average test temperature was 25℃. Each group of samples was tested in parallel three times, and the average value was taken and the test results were recorded. Table 4. Thermal conductivity test results ; As can be seen from the analysis of Table 4, the thermal conductivity of Examples 3 and 4 is 0.021 W / (m·K) and 0.018 W / (m·K) respectively, which proves that the aerogel-based powder prepared by the present invention has excellent thermal insulation performance. The thermal conductivity of Example 4 is lower than that of Example 3. The reason for this is that Example 4 has a higher content of thermal expansion capsules and hydrophobic silica, a more developed hierarchical porous structure, and a longer heat conduction path. The thermal conductivity of Comparative Example 1 was 0.032 W / (m·K), which was 52.4% higher than that of Example 3. This proves that the lack of preparation of the water-based construction composition resulted in uneven dispersion of thermal expansion capsules, poor pore formation effect, lack of micron-level cavities inside the aerogel, and failure to effectively construct a multi-level porous thermal insulation structure. The thermal conductivity of Comparative Example 2 is comparable to that of Example 3, indicating that the presence or absence of dynamic disulfide bonds has little effect on the thermal conductivity, and the thermal insulation performance mainly depends on the hierarchical porous structure.

[0013] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. An amorphous silicon-based aerogel powder prepared by microwave drying, characterized in that, It consists of the following components by weight percentage: 28-30% tetraethyl orthosilicate, 23-25% anhydrous ethanol, 10-12% aqueous building block, 4-6% hexamethyldisilazane, 0.7-1% γ-mercaptopropyltriethoxysilane, 1-1.5% hydrogen peroxide solution, 0.3-0.5% acetic acid solution, 2-3% hydrochloric acid solution, 3-4% ammonia and 17-28% deionized water.

2. The amorphous silicon-based aerogel powder prepared by microwave drying according to claim 1, characterized in that, The water-based construct composition comprises the following components by weight percentage: 19% fumed silica, 3% hexamethyldisilazane, 2% anhydrous ethanol, 21% chopped glass fiber, 2.4% acrylonitrile, 1.6% methyl methacrylate, 0.08% azobisisobutyronitrile, 3.5% isobutane, 1.5% nano silica, 1% sodium dodecyl sulfate, 15% SEBS-g-MAH, 10% naphthenic oil, 2% antioxidant 1010, 2% sodium hydroxide, 5.92% ethyl acetate, and 10% deionized water.

3. The amorphous silicon-based aerogel powder prepared by microwave drying according to claim 1, characterized in that, The concentration of the acetic acid solution is 0.5 mol / L; the concentration of the hydrochloric acid solution is 0.1 mol / L; the concentration of the ammonia solution is 0.5 mol / L; and the concentration of the hydrogen peroxide solution is 30 wt%.

4. The amorphous silicon-based aerogel powder prepared by microwave drying according to claim 1, characterized in that, The method for preparing the water-based construct composition includes the following steps: A1: Place fumed silica in a vacuum drying oven at a temperature of 110-130℃ and a vacuum of -0.08 to -0.10 MPa for 1.5-2.5 hours. After drying, transfer it to a reactor equipped with a reflux condenser, add anhydrous ethanol, set the stirring speed to 200-300 rpm, and stir for 12-18 minutes. Add hexamethyldisilazane while stirring, heat to 55-65℃, and stir for 3.5-4.5 hours. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with anhydrous ethanol. Then place the filter cake in a vacuum drying oven at a temperature of 75-85℃ and a vacuum of -0.08 to -0.10 MPa for 3.5-4.5 hours. Pass the filter cake through a 200-mesh sieve to obtain hydrophobic silica. A2: Acrylonitrile, methyl methacrylate, and azobisisobutyronitrile are added to ethyl acetate. The stirring speed is set to 180-220 rpm, and the mixture is heated to 65-75℃ under nitrogen protection. The mixture is stirred for 4.5-5.5 h to obtain a copolymer solution. The copolymer solution is heated to 42-48℃, and the stirring speed is set to 180-220 rpm. The mixture is stirred for 12-18 min to obtain a wall material solution. Isobutane is liquefied through a low-temperature condenser and kept in liquid state at -12 to -8℃. The wall material solution is transferred to a high-pressure emulsification kettle with jacket cooling. The temperature is set to -7 to -3℃, and the stirring speed is set to 450-550 rpm. Under stirring, the wall material solution is injected into the liquid isobutane at a rate of 0.25-0.35 kg / min using a metering pump. The mixture is stirred and emulsified for 25-35 min to obtain a primary emulsion. A3: Add nano-silica and sodium dodecyl sulfate to pure water, set the stirring speed to 350-450 rpm, and stir for 18-22 min to obtain a dispersion, wherein the mass ratio of nano-silica, sodium dodecyl sulfate and pure water is 1.5:1:

20. Heat the primary emulsion to 22-28℃, and use a metering pump to inject the dispersion into the emulsion at a rate of 0.18-0.22 kg / min. Set the stirring speed to 550-650 rpm and stir for 12-18 min. Then heat to 62-68℃ and continue stirring for 3.5-4.5 h. After the reaction is complete, cool to room temperature and filter using a vacuum filtration device. Wash the filter cake three times with deionized water. Place the filter cake in a vacuum drying oven, set the temperature to 42-48℃, the vacuum degree to -0.08 to -0.10 MPa, and dry for 7-9 h. Pass through a 200-mesh sieve to obtain thermally expanded capsules. A4: Add chopped glass fibers and thermal expansion capsules to a high-speed mixer, set the speed to 220-280 rpm, the mixing temperature to 22-28℃, and mix for 8-12 minutes. During the mixing process, use intermittent forward and reverse stirring, rotating forward for 1.5-2.5 minutes and then reverse for 1.5-2.5 minutes to obtain a multifunctional powder premix. Place naphthenic oil in a heating kettle with jacket heating and nitrogen protection, preheat to 115-125℃, add SEBS-g-MAH and antioxidant 1010, set the stirring speed to 180-220 rpm, and stir for 20-25 minutes to obtain a SEBS-g-MAH naphthenic oil solution. A5: Cool the SEBS-g-MAH naphthenic oil solution to 55-65℃, set the stirring speed to 180-220 rpm, and use a metering pump to inject the SEBS-g-MAH naphthenic oil solution into the multifunctional powder premix at a rate of 1-1.4 kg / min while stirring. The mixing temperature is 42-48℃. After the addition is complete, continue stirring for 30-40 min to obtain the oil-filled functional slurry. Add sodium hydroxide to 50% of the formula amount of deionized water, set the stirring speed to 220-280 rpm, and stir until completely dissolved to obtain a sodium hydroxide solution. Transfer the oil-filled functional slurry to a closed emulsification kettle with jacket heating, heat to 120-130℃, and use a metering pump to inject the sodium hydroxide solution into the oil-filled functional slurry at a rate of 0.35-0.45 kg / min. Set the emulsification kettle speed to 450-550 rpm and stir for 22-28 min to obtain the initial mixture. A6: Lower the temperature of the emulsification tank to 85-95℃, and inject 50% of the formula amount of preheated deionized water at 85-95℃ into the initial mixture at a rate of 0.55-0.65 kg / min using a metering pump. After injection, lower the temperature of the emulsification tank to 45-55℃, and continue stirring and maturing at 450-550 rpm for 25-35 min. Then, cool to room temperature using a plate heat exchanger, add hydrophobic silica, set the stirring speed to 250-350 rpm, and stir for 12-18 min. After stirring, pass through a 100-mesh sieve to obtain the water-based construct composition, which should be used within 48 hours.

5. The method for preparing amorphous silicon-based aerogel powder by microwave drying according to claim 1, characterized in that, Includes the following steps: S1: Add tetraethyl orthosilicate, 2 / 3 of the formula amount of anhydrous ethanol and 50% of the formula amount of deionized water to a reaction vessel, set the stirring speed to 300 rpm, add hydrochloric acid solution dropwise while stirring, and hydrolyze at 32℃ for 45 min to obtain silica sol. Add γ-mercaptopropyltriethoxysilane and 1 / 3 of the formula amount of anhydrous ethanol to a reaction vessel equipped with a reflux condenser, set the stirring speed to 250 rpm, introduce nitrogen protection, heat to 45℃, and stir for 12 min to obtain mercaptosilane solution. S2: Transfer the mercaptosilane solution to the reaction vessel, set the stirrer speed to 250 rpm, and use a constant flow pump to add hydrogen peroxide solution dropwise to the mercaptosilane solution at a rate of 0.15 kg / min. During the dropwise addition, control the reaction temperature to not exceed 55℃. After the dropwise addition is completed, raise the temperature to 60℃, keep the stirrer speed constant, and continue stirring for 3.5 h. After the reaction is completed, raise the temperature to 90℃, keep it at the temperature and stir for 60 min to decompose the residual hydrogen peroxide. Then add acetic acid solution, stir at 200 rpm for 12 min, and cool to room temperature to obtain the reaction solution. S3: Mix the reaction solution with the remaining amount of deionized water in the formula, set the stirrer speed to 250 rpm, stir for 5 min, add it to the silica sol after stirring, set the stirrer speed to 350 rpm, and continue stirring for 18 min to obtain a dynamic bond hybrid silica sol. Add the water-based building composition to the dynamic bond hybrid silica sol, set the stirrer speed to 450 rpm, and stir for 25 min. After stirring, set the ultrasonic power to 300 W and the ultrasonic frequency to 20 kHz, and ultrasonically disperse for 12 min. After ultrasonic dispersion, cool to room temperature, then set the stirrer speed to 450 rpm, and slowly add ammonia water dropwise while stirring. After the addition is complete, stop stirring and let the gel stand to obtain a dynamic bond hybrid composite wet gel. S4: Add anhydrous ethanol and pure water to the reactor and mix and stir at 200 rpm for 5 min to obtain an ethanol / water mixture, wherein the volume ratio of ethanol to pure water is 1:

1. Add anhydrous ethanol and n-hexane to the reactor and mix and stir at 200 rpm for 5 min to obtain an ethanol / n-hexane mixture, wherein the volume ratio of anhydrous ethanol to n-hexane is 1:

1. Preheat the ethanol / water mixture to 50℃. Then, add the dynamic bond hybrid composite wet gel to the preheated ethanol / water mixture and age for 14 h. After aging, transfer it to the ethanol / n-hexane mixture and continue aging for 7 h. After the continued aging, transfer it to n-hexane and age for a final 7 h. After the final aging, the displacement wet gel is obtained. S5: Hexamethyldisilazane was added to n-hexane to obtain a modified solution, wherein the mass ratio of hexamethyldisilazane to n-hexane was 1:

25. The displacement wet gel was then immersed in the modified solution and soaked at room temperature for 2.5 hours. After soaking, the modified solution was drained, and the wet gel was transferred separately to a microwave drying device. A segmented program was set for microwave drying. The first stage temperature was 50℃, the microwave power was 200W, and the drying time was 30 minutes. The second stage temperature was 70℃, the microwave power was 350W, and the drying time was 25 minutes. The third stage temperature was 90℃, the microwave power was 500W, and the drying time was 15 minutes. The fourth stage temperature was 110℃, the microwave power was 600W, and the drying time was 10 minutes. After drying, a block aerogel was obtained. S6: The blocky aerogel is transferred to a jaw crusher and coarsely crushed into particles with a diameter of less than 5 mm. Then, it is finely crushed using an air jet mill at a crushing pressure of 0.7 MPa and a classifying speed of 4000 rpm. The aerogel base powder is obtained through multi-stage cyclone separation. The aerogel base powder is then passed through a 200-mesh sieve to obtain amorphous silicon-based aerogel base powder prepared by microwave drying.

6. The amorphous silicon-based aerogel powder prepared by microwave drying according to claim 2, characterized in that, The specific surface area of ​​the fumed silica is 200 m². 2 / g, with a native particle size of 12nm.

7. The amorphous silicon-based aerogel powder prepared by microwave drying according to claim 2, characterized in that, The chopped glass fibers have a length of 80 μm and a diameter of 6 μm.

8. The amorphous silicon-based aerogel powder prepared by microwave drying according to claim 2, characterized in that, The SEBS-g-MAH has a styrene content of 20wt%, a maleic anhydride grafting rate of 1.5wt%, and a melt index of 8g / 10min measured at 230℃ and 5kg load.